Necessary heresies challenging the narratives distorting contemporary UK defence - Bronk, Justin (Whitehall paper, 2021)
"Emerging technologies are changing how militaries are structured and how they will fight in the future. However, many of the interpretations currently dominating the discourse in UK Defence about how these technologies and supposedly novel adversary activities will shape the future operating environment are provably false. Necessary Heresies is an attempt to correct some of these misleading narratives before they drive acquisition and force-design decisions that undermine the British Armed Forces."